INNOVATIVE APPROACHES IN LANGUAGE AND LITERARY SCIENCES IN THE PROCESS OF TRAINING HIGHLY QUALIFIED PERSONNEL IN THE CONDITIONS OF GLOBALIZATION (Universal International Scientific Journal, 2026)
This article discusses the impact of globalization on the education system, in particular, the role of language and literature in the training of highly qualified personnel, as well as the importance of innovative approaches. The issues of forming modern competencies based on digital transformation, artificial intelligence, interactive methods and an integrated education model are analyzed. The educational role of language and literature in the spiritual and moral protection of young people in the conditions of freedom of information is also substantiated.
Keywords: globalization; innovative education; digital transformation